Consultation between the United States and Pakistan after the Soviet Union’s invasion of Afghanistan - yang xiuqin,; Jiang, Lan (Pacific International Journal, 2024)
On December 25, 1979, after the Soviet Union invaded Afghanistan, Pakistan became a frontline country to contain the Soviet Union’s southward expansion. In view of its goals of global containment of the Soviet Union, maintaining stability in the South Asian region, and preventing South Asian countries from swinging to the Soviet Union, the United States actively seeks cooperation of Pakistan to curb USSR expansionism and increase the security costs of invading the Soviet Union in Afghanistan. Due to the fact that the amount of the Carter administration’s aid program for Pakistan was far from what the Zia Haq administration wish to get, and the Carter administration had repeatedly suppressed Pakistan due to nuclear issues, coupled with the fact that the United States had not explicitly supported Pakistan in all previous Indo-Pak wars. The combination of multiple factors resulted in the Carter administration not attracting Pakistan to promise cooperation in resisting the Soviet Union.